2015
DOI: 10.1556/aphysiol.102.2015.1.6
|View full text |Cite
|
Sign up to set email alerts
|

Pre- and post-estrogen administration in global cerebral ischemia reduces blood-brain barrier breakdown in ovariectomized rats

Abstract: The aim of present study was to determine the effect of estrogen treatment on blood-brain barrier permeability in rats with induced global cerebral ischemia. The study included six-month-old female Sprague-Dawley rats which were divided into the following groups: Control-Ischemia-Reperfusion (C + I-R); Ovariectomy-Ischemia-Reperfusion (Ovx + I-R); Ovariectomy + Estrogen + Ischemia-Reperfusion (Ovx + E + I-R); Ovariectomy + IschemiaReperfusion + Estrogen (Ovx + I-R + E). Ischemia-reperfusion was induced by clam… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 23 publications
0
1
0
Order By: Relevance
“…Flow response to hypercapnia relies on arteriolar smooth muscle relaxation ( Mellander, 1989 ) and previous ex vivo report using the Pressurized Arteriograph Chamber showed that 30 days following Ovx, myogenic reactivity and passive lumen diameter of penetrating arterioles were unaffected while myogenic tone and Blood–Brain Barrier (BBB) permeability to Lucifer Yellow were increased when compared to specimens harvested from control subjects ( Cipolla et al, 2009 ). In a different study, ex vivo spectrophotometry revealed increased BBB permeability to Evans Blue following global ischemia-reperfusion in Ovx female rats 3 weeks following surgery ( Uzum et al, 2015 ). In both cases, ERT rescued the increase in BBB permeability.…”
Section: Discussionmentioning
confidence: 99%
“…Flow response to hypercapnia relies on arteriolar smooth muscle relaxation ( Mellander, 1989 ) and previous ex vivo report using the Pressurized Arteriograph Chamber showed that 30 days following Ovx, myogenic reactivity and passive lumen diameter of penetrating arterioles were unaffected while myogenic tone and Blood–Brain Barrier (BBB) permeability to Lucifer Yellow were increased when compared to specimens harvested from control subjects ( Cipolla et al, 2009 ). In a different study, ex vivo spectrophotometry revealed increased BBB permeability to Evans Blue following global ischemia-reperfusion in Ovx female rats 3 weeks following surgery ( Uzum et al, 2015 ). In both cases, ERT rescued the increase in BBB permeability.…”
Section: Discussionmentioning
confidence: 99%